Piper nigrum Oil – Determination of Selected Terpenes for Quality Evaluation - Wang, Mei; Chittiboyina, Amar G.; Parcher, Jon F.; Ali, Zulfiqar; Ford, Paul; Zhao, Jianping; Avula, Bharathi; Wang, Yan-Hong; Khan, Ikhlas A. (Planta Medica, 2019)
The growing demand and commercial value of black pepper (Piper nigrum) has resulted in considerable interest in developing suitable and cost-effective methods for chemical characterization and quality evaluation purposes. In the current study, an extensive set of oil samples (n = 23) that were extracted by steam distillation from black pepper seeds was investigated to compare the chemical profiles of samples originating from nine major producing countries, as well as to identify potential chemical markers for quality evaluation. The twenty-two most abundant volatile compounds, mainly terpenes, in these oils were determined by conventional GC/MS analysis. Principal component analysis with this set of data revealed distinct clusters for samples that originated from China and Malaysia. Relatively low concentrations of sabinene (< 0.2%) and high concentrations of 3-carene (10.9 – 21.1%) were observed in these samples, respectively, compared to oil samples from other countries. The enantiomeric distributions of key terpene markers, viz., β-pinene, sabinene, limonene, and terpinen-4-ol, were determined by chiral GC/MS analysis. Interestingly, for these four monoterpenes, levo-isomers were found to be predominant, emphasizing the highly conserved enzymatic processes occurring in P. nigrum. Moreover, consistent enantiomeric ratios ((−) isomer/(+) isomer) of 92.2 ± 3.0% for β-pinene, 94.8 ± 2.8% for sabinene, 60.7 ± 1.1% for limonene, and 78.3 ± 1.3% for terpinen-4-ol were observed, independent of geographical location. These results demonstrate the potential of using stereospecific compositions as chiral signatures for establishing the authenticity and quality of black pepper oil.
Keywords: Piper nigrum; Piperaceae; conventional GC/MS; chiral GC/MS; enantiomeric distribution; authenticity; quality evaluation